Semantic Effects in Morphological Priming: The Case of Hebrew Stems. (December 2019) - Farhy, Yael; Veríssimo, João
To what extent is morphological representation in different languages dependent on semantic information? Unlike Indo-European languages, the Semitic mental lexicon has been argued to be purely "morphologically driven", with complex stems represented in a decomposed format (root + vowel pattern) irrespectively of their semantic properties. We have examined this claim by comparing cross-modal root-priming effects elicited by Hebrew verbs of a productive, open-ended class (Piel) and verbs of a closed-class (Paal). Morphological priming effects were obtained for both verb types, but prime-target semantic relatedness interacted with class, and only modulated responses following Paal, but not Piel primes. We explain these results by postulating different types of morpho-lexical representation for the different classes: structured stems, in the case of Piel, and whole-stems (which lack internal morphological structure), in the case of Paal. We conclude that semantic effects in morphological priming are also obtained in Semitic languages, but they are crucially dependent on type of morpho-lexical representation.